Bernhard Korner, Orte des Glaubens - loci theologici. Studien zur theologischen Erkennt- nislehre, Wiirzburg: Echter Verlag GmbH 2014, s. 265, ISBN 978-3-429-03752-9. - Słocińska, Maria (Poznańskie Studia Teologiczne, 2015)
Bernhard Korner, Orte des Glaubens - loci theologici. Studien zur theologischen Erkennt- nislehre, Wiirzburg: Echter Verlag GmbH 2014, s. 265, ISBN 978-3-429-03752-9.